2022
DOI: 10.1021/acs.nanolett.2c00893
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Encapsulation Membrane in Operando Scanning Transmission Electron Microscopy

Abstract: Nanoscale tailoring of catalytic materials and Libattery alternatives has elevated the importance of in situ gas-phase electron microscopy. Such advanced techniques are often performed using an environmental cell inserted into a conventional S/TEM setup, as this method facilitates concurrent electrochemical and temperature stimulations in a convenient and costeffective manner. However, these cells are made by encapsulating gas between two insulating membranes, which introduces additional electron scattering. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…It has been already found that reducing the thickness of these membranes or substituting the material can improve the image resolution. 20 When innovative developments are contemplated, many avenues can be considered. Previously we depicted the importance and the use of residual gas analyzer systems in several in situ ETEM studies.…”
Section: ■ Advances In In Situ and Operando Gas Cellmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been already found that reducing the thickness of these membranes or substituting the material can improve the image resolution. 20 When innovative developments are contemplated, many avenues can be considered. Previously we depicted the importance and the use of residual gas analyzer systems in several in situ ETEM studies.…”
Section: ■ Advances In In Situ and Operando Gas Cellmentioning
confidence: 99%
“…The SiN x membranes incorporated in this setup trigger additional electron scattering, resulting in a reduction of the resolution. It has been already found that reducing the thickness of these membranes or substituting the material can improve the image resolution …”
Section: Summary and Prospectsmentioning
confidence: 99%
See 3 more Smart Citations